Metagenomic insights to understand transient influence of Yamuna River on taxonomic and functional aspects of bacterial and archaeal communities of River Ganges - Samson, Rachel; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Rajput, Vinay; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Science of the Total Environment, 2019)
River confluences are interesting ecosystems to investigate for their microbial community structure and functional potentials. River Ganges is one of the most important and holy river of India with great mythological history and religious significance. The Yamuna River meets Ganges at the Prayagraj (formerly known as Allahabad), India to form a unique confluence. The influence of Yamuna River on taxonomic and functional aspects of microbiome at this confluence and its downstream, remains unexplored. To unveil this dearth, whole metagenome sequencing of the microbial (bacterial and archaeal) community from the sediment samples of December 2017 sampling expedition was executed using high throughput MinION technology. Results revealed differences in the relative abundance of bacterial and archaeal communities across the confluence. Grouped by the confluence, a higher abundance of Proteobacteria and lower abundance of Bacteroidetes and Firnacutes was observed for Yamuna River (G15Y) and at immediate downstream of confluence of Ganges (G15DS), as compared to the upstream, confluence, and farther downstream of confluence. A similar trend was observed for archaeal communities with a higher abundance of Euryarchaeoto in G15Y and G15DS, indicating Yamuna River's influence. Functional gene(s) analysis revealed the influence of Yamuna River on xenobiotic degradation, resistance to toxic compounds, and antibiotic resistance interceded by the autochthonous microbes at the confluence and succeeding downstream locations. Overall, similar taxonomic and functional profiles of microbial communities before confluence (upstream of Ganges) and farther downstream of confluence, suggested a transient influence of Yamuna River. Our study is significant since it may be foundational basis to understand impact of Yamuna River and also rare event of mass bathing on the microbiome of River Ganges. Further investigation would be required to understand, the underlying cause behind the restoration of microbial profiles post-confluence farther zone, to unravel the rejuvenation aspects of this unique ecosystem. (C) 2019 Elsevier B.A. All rights reserved.
Keywords: Confluence zone; Ganges; Metagenomics; Transient influence; Yamuna

Metagenome sequencing to unveil microbial community composition and prevalence of antibiotic and metal resistance genes in hypersaline and hyperalkaline Lonar Lake, India - Chakraborty, Jaya; Sapkale, Vibhavari; Shah, Manan; Rajput, Vinay; Mehetre, Gajanan; Agawane, Sachin; Kamble, Sanjay; Dharne, Mahesh (Ecological Indicators, 2020)
Lonar Lake (India) is a hyperalkaline and hypersaline soda lake encompassing unique microbial composition and functions. This ecosystem has not been explored for taxonomic diversity and functional aspects (with emphasis on antibiotic and metal resistance genes) using whole metagenome sequencing for multiple years. Bacterial diversity analysis during year 2013, 2016, and 2018 depicted differences in the dominance of Proteobacteria, Firmicutes and Bacteroidetes. For archaeal diversity, a similar pattern persisted with higher abundance of Euryarchaeota. Functional metagenome analyses, indicated presence of antibiotic resistance gene (ARG) and metal resistance gene (MRG) profiles in the lake. A wider continuum of resistance genes with dominant ARG types as multidrug resistance efflux pumps and beta-lactams were also observed. The lake resistome demonstrated fluoroquinolone and acriflavine resistance genes indicating sewage water contamination in the lake. The MRGs linked with resistance to toxic metals (arsenic, cobalt, cadmium, copper, and zinc) and cation efflux protein CusA and cobalt-zinc-cadmium resistance protein revealed metal contamination. This study could be a baseline for understanding prevalence of antibiotic and metal resistance mechanisms resulting from various anthropogenic activities nearby lake, and find integrated approaches for conservation of the precious Lonar Lake ecosystem.
Keywords: Archaeal diversity; ARGs; Bacterial diversity; Illumina sequencing; Lonar lake; MRGs

Metagenomic analysis of a mega-city river network reveals microbial compositional heterogeneity among urban and peri-urban river stretch - Yadav, Rakeshkumar; Rajput, Vinay; Dharne, Mahesh (Science of the Total Environment, 2021)
The rivers in the megacities face a constant inflow of extremely polluted wastewaters from various sources, and their influence on the connected peri-urban river is still poorly understood. The riverine system in Pune consists of Rivers Mula, Ramnadi, Pawana, Mutha, and Mula-Mutha, traversing through the urban settlements of Pune before joining River Bhima in the peri-urban region. We used MinION-based metagenomic sequencing to generate a comprehensive understanding of the microbial diversity differ-ences between the urban and peri-urban zones, which has not been explored at the meta scale until date. The taxonomic analysis revealed significant enrichment of pollution indicators microbial taxa (Welsch's t-test, p < 0.05, Benjamini-Hochberg FDR test) such as Bacteriodetes, Firmicutes, Spirochaetes, Synergistetes, Euryarcheota in the urban waters as compared to peri-urban waters. Further, the peri-urban waters showed a significantly higher prevalence of ammonium oxidising archaeal groups such as Nitrososphaeraceae (Student's t-test p-value <0.05 with FDR correction), thereby probably suggesting the influence of agricultural runoffs. Besides, the microbial community diversity assessment also indicated the significant dissimilarity in the microbial community of urban and peri-urban waters. Overall, the analysis predicted 295 virulence genes mapping to 38 different path-ogenic bacteria in the riverine system. Moreover, the higher genome coverage (at least 60%) for priority patho-gens such as Pseudomonas, Klebsiella, Acinetobacter, Escherichia, Aeromonas in the sediment metagenome consolidates their dominance in this riverine system. To conclude, our investigation showed that the unre-strained anthropogenic and related activities could potentially contribute to the overall dismal conditions and in-fluence the connected riverine stretches on the outskirts of the city . (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Industrialisation; Peri-urban; Riverine system; Urbanisation; Virulence factors

Metagenomic analysis reveals genetic insights on biogeochemical cycling, xenobiotic degradation, and stress resistance in mudflat microbiome - Mohapatra, Madhusmita; Yadav, Rakeshkumar; Rajput, Vinay; Dharne, Mahesh S.; Rastogi, Gurdeep (Journal of Environmental Management, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Mudflats are highly productive coastal ecosystems that are dominated by halophytic vegetation. In this study, the mudflat sediment microbiome was investigated from Nalabana Island, located in a brackish water coastal wetland of India; Chilika, based on the MinION shotgun metagenomic analysis. Bacterial, archaeal, and fungal communities were mostly composed of Proteobacteria (38.3%), Actinobacteria (20.7%), Euryarchaeota (76.1%), Candidatus Bathyarchaeota (6.8%), Ascomycota (47.2%), and Basidiomycota (22.0%). Bacterial and archaeal community composition differed significantly between vegetated mudflat and un-vegetated bulk sediments. Carbon, nitrogen, sulfur metabolisms, oxidative phosphorylation, and xenobiotic biodegradation were the most common microbial functionalities in the mudflat metagenomes. Furthermore, genes involved in oxidative stresses, osmotolerance, secondary metabolite synthesis, and extracellular polymeric substance synthesis revealed adaptive mechanisms of the microbiome in mudflat habitat. Mudflat metagenome also revealed genes involved in the plant growth and development, suggesting that microbial communities could aid halophytic vegetation by providing tolerance to the abiotic stresses in a harsh mudflat environment. Canonical correspondence analysis and co-occurrence network revealed that both biotic (vegetation and microbial interactions) and abiotic factors played important role in shaping the mudflat microbiome composition. Among abiotic factors, pH accounted for the highest variance (20.10%) followed by available phosphorus (19.73%), total organic carbon (9.94%), salinity (8.28%), sediment texture (sand) (6.37%) and available nitrogen (5.53%) in the mudflat microbial communities. Overall, this first metagenomic study provided a comprehensive insight on the community structure, potential ecological interactions, and genetic potential of the mudflat microbiome in context to the cycling of organic matter, xenobiotic biodegradation, stress resistance, and in providing the ecological fitness to halophytes. These ecosystem services of the mudflat microbiome must be considered in the conservation and management plan of coastal wetlands. This study also advanced our understanding of fungal diversity which is understudied from the coastal lagoon ecosystems.

Metagenomic exploration reveals a differential patterning of antibiotic resistance genes in urban and peri-urban stretches of a riverine system - Rajput, Vinay; Yadav, Rakeshkumar; Dharne, Mahesh S. (Environmental Science and Pollution Research, 2021)
{Antimicrobial resistance in the riverine ecosystem of urban areas is an alarming concern worldwide, indicating the importance of molecular monitoring to understand their patterning in urban and peri-urban areas. In the present study, we evaluated the influence of urban rivers on the connected peri-urban rivers of a riverine system of India in the context of antibiotic resistance genes. The rivers traversing through urban (Mula, Mutha, Pawana, and Ramnadi) and peri-urban stretches (Bhima and Indrayani) form the riverine system of Pune district in Maharashtra, India. The MinION-based shotgun metagenomic analysis revealed the resistome against 26 classes of antibiotics, including the last line of antibiotics. In total, we observed 278 ARG subtypes conferring resistance against multiple drugs (40%), bacitracin (10%), aminoglycoside (7.5%), tetracycline (7%), and glycopeptide (5%). Further, the alpha diversity analysis suggested relatively higher ARG diversity in the urban stretches than peri-urban stretches of the riverine system. The NMDS (non-metric multidimensional scaling) analysis revealed significant differences with overlapping similarities (stress value = 0.14
Keywords: Antibiotic resistance; MinION; Peri-urban rivers; Urbanization

Metagenomic mining of Indian river confluence reveal functional microbial community with lignocelluloytic potential - Rajput, Vinay; Samson, Rachel; Yadav, Rakeshkumar; Dastager, Syed; Khairnar, Krishna; Dharne, Mahesh (3 Biotech, 2022)
Microbial carbohydrate-active enzymes (CAZyme) can be harnessed for valorization of Lignocellulosic biomass (LCB) to value-added chemicals/products. The two Indian Rivers Ganges and the Yamuna having different origins and flow, face accumulation of carbon-rich substrates due to the discharge of wastewater from adjoining paper and pulp industries, which could potentially contribute to the natural enrichment of LCB utilizing genes, especially at their confluence. We analyzed CAZyme diversity in metagenomic datasets across the sacred confluence of the Rivers Ganges and Yamuna. Functional annotation using CAZyme database identified a total of 77,815 putative genes with functional domains involved in the catalysis of carbohydrate degradation or synthesis of glycosidic bonds. The metagenomic analysis detected similar to 41% CAZymes catalyzing the hydrolysis of lignocellulosic biomass polymers- cellulose, hemicellulose, lignin, and pectin. The Beta diversity analysis suggested higher CAZyme diversity at downstream region of the river confluence, which could be useful niche for culture-based studies. Taxonomic origin for CAZymes revealed the predominance of bacteria (97%), followed by archaea (1.67%), Eukaryota (0.63%), and viruses (0.7%). Metagenome guided CAZyme diversity of the microflora spanning across the confluence of Ganges-Yamuna River, could be harnessed for biomass and bioenergy applications.
Keywords: CAZymes; Confluence (Sangam); Lignocellulosic; River Ganges; River Yamuna